Pengaruh Latihan Keseimbangan Terhadap Keseimbangan Postural pada Lansia - Widiyanta, Fauzyah Azzahra; Sidarta, Nuryani (Fakultas Kedokteran Universitas Trisakti, 2025)
Background The elderly have a higher potential for injury due to reduced body stability. In Indonesia, the incidence of elderly falls is 12.9%. Factors contributing to the increased risk of falls include biological changes such as aging and sedentary lifestyle habits. Balance training is one form of exercise that is considered effective in improving postural stability in the elderly. However, the success of this exercise is highly dependent on the duration of its application. Therefore, in this study, we aimed to evaluate the effect of balance training on postural stability with a two-week training program. Methods This study used a quasi-experimental design involving 25 elderly individuals aged more than 60 years. Consecutive non-random sampling technique was applied in the selection of participants. The balance training program was implemented three times per week for a period of two weeks. The exercise protocol was based on the guidelines released by the American College of Sports Medicine (ACSM). To assess postural stability, the Timed Up and Go Test instrument was used, which was administered before and after the exercise program. Data analysis was performed using the Wilcoxon test method with a significance limit of p<0.05. Results The findings of this study indicated that the elderly group over 70 years old dominated the study participants, with the proportion of women at 56% and men at 44%. The results of the postural balance evaluation revealed that 64% of the subjects showed a low level of balance, especially in the elderly over 70 years old with female gender. Bivariate analysis gave a p value = 0.00, indicating a significant effect of a balance training program performed three times a week with an interval of days for two consecutive weeks on improving postural stability in the elderly. Conclusions Balance training 3 times a week with alternate days for 2 consecutive weeks has an effect on improving postural balance in the elderly.